2004
DOI: 10.1038/sj.embor.7400279
|View full text |Cite
|
Sign up to set email alerts
|

Oct4 is required for primordial germ cell survival

Abstract: Previous studies have shown that Oct4 has an essential role in maintaining pluripotency of cells of the inner cell mass (ICM) and embryonic stem cells. However, Oct4 null homozygous embryos die around the time of implantation, thus precluding further analysis of gene function during development. We have used the conditional Cre/loxP gene targeting strategy to assess Oct4 function in primordial germ cells (PGCs). Loss of Oct4 function leads to apoptosis of PGCs rather than to differentiation into a trophectoder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
381
1
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(417 citation statements)
references
References 23 publications
(48 reference statements)
18
381
1
8
Order By: Relevance
“…In this work, we investigated the role of Sox2 during mouse gametogenesis. Our results reveal that Sox2 deletion during the establishment of germ cell lineage impairs PGC development, as previously shown for Prdm14 [16], Oct4 [17,18], and Nanog [19]. We also found that Sox2 is essential for PGC proliferation in vivo and in vitro, and that it affects the expression of genes which are critical for their development.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…In this work, we investigated the role of Sox2 during mouse gametogenesis. Our results reveal that Sox2 deletion during the establishment of germ cell lineage impairs PGC development, as previously shown for Prdm14 [16], Oct4 [17,18], and Nanog [19]. We also found that Sox2 is essential for PGC proliferation in vivo and in vitro, and that it affects the expression of genes which are critical for their development.…”
Section: Introductionsupporting
confidence: 65%
“…These deleters, obtained by knocking Cre into the TNAP (tissue nonspecific alkaline phosphatase) locus, mediate Cre excision in PGCs between 9.0 and 10.5 dpc [17,30] (Fig. 1D).…”
Section: Sox2 Is Required For Pgc Development and Pluripotencymentioning
confidence: 99%
“…14,16,26 The presence of this protein is essential for pluripotency of embryonic stem cells; and early in development, expression becomes confined to the germ cell lineage. Loss of OCT3/4 expression in mouse primordial germ cells leads to apoptosis, 27 and thus is required for their survival. Upon differentiation of primordial germ cells/gonocytes to either pre-spermatogonia or oogonia, OCT3/4 is lost.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult, Oct4 is exclusively expressed in germ cells, and had been detected in stem-cell populations such as bone marrow multipotent adult progenitors, haematopoietic stem cells, and stem cells that reside in epidermal basal layers 78,79 . More recent studies demonstrate that OCT4 is essential for germ-cell maintenance, but dispensable for somatic stem-cell self-renewal 80,81 . The importance of strictly maintaining Oct4 expression levels has been demonstrated both in vitro and in vivo: even a two-fold change in OCT4 protein abundance can cause ES cells to lose pluripotency 82 , and ectopic Oct4 expression promotes epithelial dysplasia in transgenic mice 83 .…”
Section: Oct4 Regulation By O 2 Levelsmentioning
confidence: 99%